Flavonoids and Organic Acids Affect Phase II Metabolism based on the Regulation of UGT1A1 Expression and Function - Zhang, Lin; Zhang, Xuerong; Wang, Caiyan (Current Computer - Aided Drug Design, 2025)
BackgroundExogenous substances modulate metabolism by regulating the expression and function of UDP-glycosyltransferases (UGTs). However, the exact mechanism in the intestine was rarely understood. Herein, we explored the effects of representative flavonoids and organic acids on the regulation of UGT1A1.MethodsMTT assays and western blot analysis were used to explore the effect of polyphenols. X-ray diffraction was used to reveal the catalytic mechanisms of UGTs.ResultsMTT assays showed that these compounds basically had almost no cytotoxicity, even in concentrations up to 200 μM. However, through western blot assays, UGT1A1 expression was increased after being treated with liquiritigenin and caffeic acid. Furthermore, liquiritigenin and caffeic acid enhanced the nuclear translocation of Nrf2. Moreover, a 2.5-Å crystal structure of the complex containing UGTs C-terminal domain and organic acid was solved, and the UDPGA binding pocket could be occupied by organic acid, suggesting the enzyme activity might be impaired by organic acid.ConclusionAbove all, liquiritigenin and caffeic acid maintained the metabolism balance by upregulating the expression of UGT1A1 via Nrf2 activation and inhibiting the enzyme activity in Caco-2 cells.
Keywords: mechanism